Remodeling of the Infection Chamber before Infection Thread Formation Reveals a Two-Step Mechanism for Rhizobial Entry into the Host Legume Root Hair. Issue 4 (6th February 2015) - Fournier, Joëlle; Teillet, Alice; Chabaud, Mireille; Ivanov, Sergey; Genre, Andrea; Limpens, Erik; de Carvalho-Niebel, Fernanda; Barker, David G.
Abstract : Legume root hairs remodel the interface with symbiotic rhizobia prior to initiating the tubular-growing infection thread. Abstract: In many legumes, root entry of symbiotic nitrogen-fixing rhizobia occurs via host-constructed tubular tip-growing structures known as infection threads (ITs). Here, we have used a confocal microscopy live-tissue imaging approach to investigate early stages of IT formation in Medicago truncatula root hairs (RHs) expressing fluorescent protein fusion reporters. This has revealed that ITs only initiate 10 to 20 h after the completion of RH curling, by which time major modifications have occurred within the so-called infection chamber, the site of bacterial entrapment. These include the accumulation of exocytosis ( M. truncatula Vesicle-Associated Membrane Protein721e)- and cell wall ( M. truncatula EARLY NODULIN11)-associated markers, concomitant with radial expansion of the chamber. Significantly, the infection-defective M. truncatula nodule inception-1 mutant is unable to create a functional infection chamber. This underlines the importance of the NIN -dependent phase of host cell wall remodeling that accompanies bacterial proliferation and precedes IT formation, and leads us to propose a two-step model for rhizobial infection initiation in legume RHs.